2015
DOI: 10.1353/jda.2015.0036
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rates and Foreign Direct Investment: Evidence for Sub-Saharan Africa

Abstract: This paper examines the relationship between Foreign Direct Investment (FDI) and the real exchange rate for low-income countries of Sub-Saharan Africa, using a panel data approach and Two-Stage Least Squares (2SLS) method. The results show that while the depreciation of the real exchange rate draws more FDI to Sub-Saharan African countries, the real exchange rate volatility causes greater instability in FDI inflows to these countries. The results are robust across different measures and model specifications. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Walsh and Yu (2010) suggested that FDI should flow into countries with relatively stable macroeconomic conditions and strong institutions as investors are concerned more about political instability, inflexible regulations and development indicators before considering investing in a particular country. Many past studies examining the factors of FDI had often ignored the short-run instability characteristic of FDI (Wahid et al, 2009;Suliman et al, 2015). This paper attempts to fill this gap by explaining both the short-term and long-term behaviors of FDI by focusing on the role played by real exchange on net FDI inflows in Mauritius.…”
Section: Introductionmentioning
confidence: 98%
“…Walsh and Yu (2010) suggested that FDI should flow into countries with relatively stable macroeconomic conditions and strong institutions as investors are concerned more about political instability, inflexible regulations and development indicators before considering investing in a particular country. Many past studies examining the factors of FDI had often ignored the short-run instability characteristic of FDI (Wahid et al, 2009;Suliman et al, 2015). This paper attempts to fill this gap by explaining both the short-term and long-term behaviors of FDI by focusing on the role played by real exchange on net FDI inflows in Mauritius.…”
Section: Introductionmentioning
confidence: 98%
“…A few of the connected determining dynamics embrace market growth and market size, gross fixed capital formation, carbon dioxide, renewable energy, inflation, trade openness, interest rate, and exchange rate (Acheampong et al, 2021;Akin, 2009;Aziz & Makkawi, 2012;Babatunde, 2011;Bekana, 2016;Billington, 1999;Ezeoha & Cattaneo, 2012;Faroh & Shen, 2015;Fiodendji & Evlo, 2015;Gonzalez-Perezet al, 2011;Oladipo, 2013;Okurut et al, 2012;Owusu-Antwi, 2012;Ren et al, 2014;Wafure & Nurudeen, 2010;Zhang et al, 2010). The utilization of market growth and market size as essential determinants of FDI inflows, for example, is striking in numerous empirical research studies on FDI (Acheampong & Osei, 2014;Akin, 2009;Aziz & Makkawi, 2012;Bekana, 2016;Dinda, 2014;Eregha, 2015;Ezeoha & Cattaneo, 2012;Fiodendji & Evlo, 2015;Gwenhamo, 2011;Okafor, 2015;Suliman et al, 2015;Owusu-Antwi et al, 2013;Wafure & Nurudeen, 2010). Countless empirical studies in the current journals, for instance, have frequently applied the real GDP growth (a proxy for market growth), in investigating the significance of market growth in determining the inflow of FDI into a host nation.…”
Section: Macroeconomic Determinants Of Fdimentioning
confidence: 99%
“…Bekana eventually recognized that market-rising competences were the striking determinants of FDI inflows into Ethiopia. Other academics have similarly examined the significance of market growth and market size in determining FDI inflows into a nation, especially into Sub-Saharan Africa (Fiodendji & Evlo, 2015;Hasnet, 2013;Okurut et al, 2012;Suliman et al, 2015;Wafure & Nurudeen, 2010). Similar authors have applied the population growth of a nation as a proxy for market size in determining FDI inflows into a nation (Akin, 2009;Aziz & Makkawi, 2012;Billiington, 1999).…”
Section: Macroeconomic Determinants Of Fdimentioning
confidence: 99%